Synthesis of Vinylnaphthofurans and NMR Analysis of their Photoswitching. Issue 13 (23rd March 2021) - Graça, Vânia; Berthet, Jérôme; Sousa, Céu M.; Delbaere, Stephanie; Coelho, Paulo J.
Abstract: An easy synthesis of photochromic vinylnaphthofurans by the acid‐catalyzed one‐pot reaction of naphthols with but‐2‐yne‐1, 4‐diols is described. These uncolored polyaromatic compounds are activated by UV light, at room temperature, and converted through a stilbene‐type electrocyclization into a thermally stable orange species, which can be switched back using visible light. The behavior of these photoswitches was elucidated using NMR, which allowed to identify the photoisomers and some side‐products, formed after prolonged UV irradiation. Abstract : An easy synthesis of photochromic vinylnaphthofurans by the acid‐catalyzed one‐pot reaction of naphthols with but‐2‐yne‐1, 4‐diols is described. These polyaromatic compounds switch between uncolored (Vis) and colored (UV) states at room temperature. NMR analysis of irradiated solutions allowed to identify the photoisomers and some side‐products.